2008
DOI: 10.1021/es071596u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Laser Absorption Spectroscopic Techniques for Eddy Covariance Flux Measurements of Ammonia

Abstract: An intercomparison was made between eddy covariance flux measurements of ammonia by a quantum cascade laser absorption spectrometer (QCLAS) and a lead-salt tunable diode laser absorption spectrometer (TDLAS). The measurements took place in September 2004 and again in April 2005 over a managed grassland site in Southern Scotland, U.K. These were also compared with a flux estimate derived from an "Ammonia Measurement by ANnular Denuder with online Analysis" (AMANDA), using the aerodynamic gradient method (AGM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 25 publications
2
118
0
4
Order By: Relevance
“…It is important to note that surface sampling artifacts in closed-path sensors are typically reduced by minimizing inlet length, optimizing inlet coatings, inlet heating and maintaining high flow rates through small sampling volumes or other special sampling systems (Whitehead et al, 2008;Bianchi et al, 2012). Some of these measures increase power demands and limit portability for a variety of field platforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that surface sampling artifacts in closed-path sensors are typically reduced by minimizing inlet length, optimizing inlet coatings, inlet heating and maintaining high flow rates through small sampling volumes or other special sampling systems (Whitehead et al, 2008;Bianchi et al, 2012). Some of these measures increase power demands and limit portability for a variety of field platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Although these closedpath systems are highly sensitive (ppbv or sub-ppbv), they suffer from sampling artifacts that limit precision and response time and complicate calibration methods (Whitehead et al, 2008;von Bobrutzki et al, 2010). In addition, these systems are large (usually > 100 kg) and require pumps and temperature control systems with high power consumption (usually hundreds of watts).…”
Section: J Miller Et Al: Open-path Qcl-based Ammonia Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the adsorption of NH 3 to different types of sample inlet materials at various temperatures (Yokelson et al, 2003;Shah et al, 2006;Whitehead et al, 2008). In our laboratory intercomparison between the QC-TILDAS and the TDLAS, we examined the effect of heat and humidity on NH 3 adsorption to sampling lines.…”
Section: Sampling Line Effectsmentioning
confidence: 99%
“…Historically there have been a number of field intercomparisons of both research and commercial NH3 instrumentation [1,8,44]. These studies have demonstrated that under field conditions additional complications arise which are not observed under controlled conditions in the laboratory.…”
Section: Comparison and Validation Experimentsmentioning
confidence: 99%